Таинственный сапфир апостола Петра: [роман] / Наталья Александрова - Александрова Наталья Николаевна (Артефакт & Детектив, 2015)
Экземпляры: ф9; ф10; ф11 (201510) / Инвентарный номер: 51405 / Цена: 187.00 / Сис.шифр: Р2 / Авт.знак: А 46 / ГРНТИ: 17.82.31 / ББК: 84(2Pос=Рус)6